1893 Fla. Laws 51, §1 - (:unkn) unknown (My University, 1893)
Prohibited the concealed carry any dirk, pistol, or other weapon. Violators punished by imprisonment not exceeding three months, or by fine not exceeding one hundred dollars, or both.
Keywords: CARRY - CONCEALED